APPLYING THE SUGGESTOPEDIA METHOD TO STUDENTS' READING COMPREHENSION - Nelvia Ibrahim (Jurnal Cakrawala Ilmiah, 2025)
This article aims to explain the use of the suggestopedia method in teaching reading. Students also feel bored when reading in class because they do not have a method of reading. They cannot focus on what they read during the reading activity and still have difficulty understanding the ideas in the text. There are so many teaching reading methods that teachers have applied for different reading purposes. Meanwhile, Suggestopedia is a teaching approach focusing on the teacher-learner relationship while teaching and learning in the classroom. It could be used to motivate students, particularly to read.